Javanese Culture Maintenance by Keeping Traditional Javanese Food and Beverage Name in Tegal Regency Traditional Culinary Tourism - Atrinawati Atrinawati (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2019)
Culture is human being creation as a gift from God. One of ways of maintaining culture is keeping the tradition such as the traditional culinary. As part of the traditional culinary, keeping the traditional name of food and beverage becomes an important  part of culture and language maintenane since many food and beverage today were named using international name to sound more hype. Furthermore, those traditional food and beverage name is also beneficial in supporting culinary tourism promotion, especially the traditional culinary tourism. This research shows   how Tegal Regency local people supported by Tegal Regency local government through Tegal Regency Tourism Office preserves the old-traditional [1] and introduces the new-traditional [2] food and beverage names in Tegal Regency traditional culinary tourism promotion such as Kupat Glabed, Sega Lengko, Sate Blengong, Rujak Teplak, Pilus, Kacang Bogares, Teh Poci, and Es Lontrong. The result shows that using Tegal Regency old-traditional and new-traditional food and beverage name is beneficial for maintaining Javanese culture and language, particularly Tegal culture and Javanese language with Tegal Dialect as well as gaining more profit for local people and local government from culinary tourism business.